Инструмент из АКТМ для обработки деталей из титановых сплавов обкатыванием - Розенберг, О.А.; Шейкин, С.Е.; Шульженко, А.А.; Шепелев, А.А.; Гаргин, В.Г.; Ростоцкий, И.Ю.; Ефросинин, Д.В.; Русинова, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The new technology of preparation of blank from a diamond composite heat-resistant material (АКТМ) in the form of a sphere is described. Results of tests of working element of rolling device from АКТМ at machining of titanic alloy ВТ1-0 are presented. Dependence of a roughness of a machined surface on technological modes rolling is investigated. It is established, that the resistance of wear of a deforming element from АКТМ at least 10 times more the steel.